2012
DOI: 10.3329/jbsp.v7i1.11152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ashwagandha (Withania somnifera) Root Extract On Some Serum Liver Marker Enzymes (AST, ALT) In Gentamicin Intoxicated Rats

Abstract: Background: Liver is an essential metabolic organ. It can be damaged due to prolonged use and higher doses of drugs, exposure to some chemicals, toxins, or infectious agents. Herbal plants as ashwagandha (Withania somnifera) may have free radical scavenging activity thereby can be used for the prevention and treatment of liver damage. Objective: To observe the effect of ashwagandha (Withania somnifera) root extract on gentamicin induced changes of some liver marker enzymes e,g serum aspartate amino transferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Based on the literature it was reported that ashwagandha reduced the level of SGOT level in rats. The data were corroborated with the current findings [40]. …”
Section: Measurement Of Hepatic and Cardiac Biomarkerssupporting
confidence: 90%
“…Based on the literature it was reported that ashwagandha reduced the level of SGOT level in rats. The data were corroborated with the current findings [40]. …”
Section: Measurement Of Hepatic and Cardiac Biomarkerssupporting
confidence: 90%
“…Gentamicin is a well-known potent, broad spectrum aminoglycoside antibiotic with a low cost and high effectiveness when used against Gram-negative infections (Banday et al, 2008;Salem et al, 2010). However, gentamicin use has been restricted and gentamicin is used carefully owing to its effect of causing nephrotoxicity and hepatotoxicity (Stojiljkovic and Stoiljkovic, 2006;Raju et al, 2011;Nayma et al, 2012;Masakazu et al, 2014). The present study has shown the effects of HPE and how it develops gentamicin-induced nephrotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that the hepatotoxicity of gentamicin subsequently leads to necrosis and degenerative changes in the hepatocytes (Stojiljkovic and Stoiljkovic, 2006;Nayma et al, 2012;Mahmood et al, 2014;Masakazu et al, 2014). In this study, gentamicin-administered groups (Group IV) showed remarkable degenerative changes and necrosis in the hepatocytes; mononuclear cells had infiltrated within portal areas and proliferation of Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is assumed that the reduction of SGPT value might be due to the effect of Biofield Energy Healing to the test formulation. From literature it was reported that ashwagandha reduced the level of SGPT level in rats [44]. This findings could be due to the presence of ashwagandha root extract and other minerals in the test formulation …”
Section: Measurement Of Hepatic and Cardiac Biomarkersmentioning
confidence: 89%